(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2015)
Recent art cinema has produced several experiments in the tableau that conceive entire movies based on its aesthetic. Such films blur the boundaries between cinema and installation art, and consist of a loosely connected string of tableaux which gain a degree of autonomy and therefore cannot be interpreted in the contexts of cinematic narration and dramaturgy. These films are usually categorized as slow movies, and indeed their duration has inspired the majority of their analysis in film theory. Nevertheless, I suggest that we should focus on the similarities between the tableau sequences of slow movies and the installations of moving image tableaux in order to highlight the ways they revitalise the traditional, intermedial figure of the tableau vivant in art, and foreground the single, photographic frame within moving images. Referring to recent reinterpretations of the notion of the transmedial dispositif and to the revisions of the tableau mode in art (and the ideas of Jean-François Chevrier) I propose to contest Raymond Bellour’s idea of the ‘battle of the dispositifs’ and concentrate on aspects of the complex convergences between the traditional visual arts and the new media of moving images that underlies the tableau aesthetic in post-cinema. Taking into account the implosion of the tableau vivant into a more generic tableau style, I examine a set of gestures and actions of folding together photography, painting and cinema that may define the post-cinematic ‘mise en tableau’ (via examples from the films of James Benning, Lav Diaz, Gustav Deutsch, Raúl Perrone, Apichatpong Weerasethakul and Tsai Ming-liang).